A vasutak és a dunai kikötők kapcsolata 1895-ben - Majdán, János (Közép-Európai Közlemények, 2009)
At the end of the 19th century the Danube freight traffic was performed by nine companies. In 1895 freight data were recorded at ministerial decree, and with the help of the detailed sources one can follow the fluvial and railway freight traffic of Zimony, Újvidék, Vukovár, Gombos, Baja, Komárom and Gy r. On examining the traffic of transit in Danube ports one can state that the river boats and barges were important mediators of the united economic market. The freight traffic showed the signs of the division of labour and interdependence.